ChemInform Abstract: Concise Synthesis of Carbazole‐1, 4‐quinones and Evaluation of Their Antiproliferative Activity Against HCT‐116 and HL‐60 Cells. Issue 51 (5th December 2016) - Nishiyama, Takashi; Hatae, Noriyuki; Yoshimura, Teruki; Takaki, Sawa; Abe, Takumi; Ishikura, Minoru; Hibino, Satoshi; Choshi, Tominari
Abstract: Carbazole‐1, 4‐quinone alkaloids, koeniginequinone A (IIa) and B (IIb), are obtained by a three‐step total synthesis containing tandem ring‐closing metathesis with dehydrogenation reaction as key step.